Abundance, reproduction and length of scalloped hammerhead shark Sphyrna lewini (Carcharhiniformes: Sphyrnidae) in the artisanal fishery in Golfo Dulce, Pacific of Costa Rica - Zanella, Ilena; López-Garro, Andrés (Revista de Biología Tropical, 2015)
Incidental catch of S. lewini by artisanal fishermen in Golfo Dulce, Costa Rica, suggest that this could be one of the coastal locations used by the species. This study aims to characterize the scalloped hammerhead shark population in Golfo Dulce, in order to best guide management actions for the conservation and sustainable use of the species. Fisheries-dependent biological data (size-TL, sex, reproductive status) were gathered for S. lewini between May 2010 and May 2011 in the communities of Puerto Jimenez and Pavones, Golfo Dulce during artisanal fishing trips. Catch per unit effort (CPUE) throughout the year was also estimated from catch data. We sampled a total of 315 sharks. Mean total length was estimated at 74.3±17.4cm. Both pups and juveniles were reported, which presented a male: female ratio of 1:1.2 (p>0.05). Total length and relative abundance of S. lewini had opposite tendencies, with the smallest TL (64cm) recorded during July-August, when CPUE was highest. (0.0075). Temporary closures from June to August are therefore recommended at areas of highest reported catch (Pique Fijo, Los Bajos y La Ciénaga), in order to protect newly born S. lewini, and promote the sustainability of the species in the ETPS Closures should be complemented with a long-term study that can further clarify whether Golfo Dulce is a nursery area for S. lewini.